Granulation–carbonation treatment of alkali activated steel slag for secondary aggregates production - Morone, Milena; Costa, Giulia; Georgakopoulos, Evangelos; Manovic, Vasilije; Stenardo, Stefano; Baciocchi, Renato (Springer, 2016)
In view of the EU’s circular economy strategy, there is a need to develop treatments that may allow to improve the management of industrial residues such as steel manufacturing slag, for example by producing secondary products that may be used for different applications. This work evaluates the performance of a combined carbonation and granulation treatment applied to basic oxygen furnace (BOF) steel slag with the aim of producing secondary aggregates and of storing CO2 in a solid and stable form. In order to improve the mechanical properties of the product, a solution of sodium silicate and sodium hydroxide was tested as binder instead of water in both the granulation and combined granulation–carbonation tests. The results showed that the granules produced using the alkali activator with or without CO2 addition, presented a mean size ranging from 1 to 5 mm and adequate mechanical properties for use in civil engineering applications. The maximum CO2 uptake attained was of 4% wt. for the alkali activated and carbonated granules after 60 min of treatment and 7 days curing. As for the leaching behaviour of the produced granules, an increase in the release of Cr and V was found for the product of the granulation–carbonation treatment with alkali activation. Instead, granulation with alkali activation or granulation with carbonation showed to decrease the release of Ba and Cr with regard to the untreated residues.
Keywords: Steel slag; Granulation; Carbonation; Alkali activation; CO2 storage; Leaching behaviour